2020
DOI: 10.1111/ajt.15879
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells expand after transplantation and their augmentation increases graft survival

Abstract: Myeloid‐derived suppressor cells (MDSCs) expand in an inflammatory microenvironment such as cancer and autoimmunity. To study if transplantation induces MDSCs and these cells regulate allograft survival, C57BL/6 donor hearts were transplanted into BALB/c recipients and endogenous MDSCs were characterized. The effects of adoptive transfer of transplant (tx), tumor (tm), and granulocyte‐colony stimulating factor (g‐csf)–expanded MDSCs or depletion of MDSC were assessed. MDSCs expanded after transplantation (1.7‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Interestingly, myeloid cell secreting S100A9 express the myeloid-derived suppressor cells (MDSC) associated markers CD33, CD163, and DC-SIGN. MDSC have drawn particular interest in the field of transplant immunology, as systemic inflammation mobilizes immature myeloid cells from bone marrow into the circulation and the injured tissue where they may differentiate into MDSCs [104,105]. This is consistent with a recent study that reported the natural expansion of MDSCs following heart allograft transplantation in mice that favor graft survival prolongation [106].…”
Section: Cellular Regulation Of Danger Signalssupporting
confidence: 67%
“…Interestingly, myeloid cell secreting S100A9 express the myeloid-derived suppressor cells (MDSC) associated markers CD33, CD163, and DC-SIGN. MDSC have drawn particular interest in the field of transplant immunology, as systemic inflammation mobilizes immature myeloid cells from bone marrow into the circulation and the injured tissue where they may differentiate into MDSCs [104,105]. This is consistent with a recent study that reported the natural expansion of MDSCs following heart allograft transplantation in mice that favor graft survival prolongation [106].…”
Section: Cellular Regulation Of Danger Signalssupporting
confidence: 67%
“…These associations are supported by studies in which PMN-MDSC inhibit B-cell proliferation and antibody production (Lelis, Knier) (17,18). However, MDSC are also known to expand in IC populations such as transplant recipients, and cancer patients (Lee, Feng, Cassetta) (19)(20)(21). This expansion was not apparent in vaccinated IC subjects with RBD-IgG, in whom M-MDSC and PMN-MDSC frequencies approximated those seen in immunocompetent subjects.…”
Section: Discussionmentioning
confidence: 81%
“…It is the result of interaction between donor T cells and recipient antigen-presenting cells (APCs) [ 57 ], which can be a devastating complication for as many as one-third of patients undergoing allo-HSCT [ 58 ]. Due to the unique functional characteristic of suppression to alloreactive T cell responses [ 59 ], MDSCs have stirred up interest among transplant immunologists in their potential clinical merits. Expectedly, researchers have demonstrated that GVHD can be efficiently prevented by MDSCs without influencing graft-versus-leukemia (GVL) effect in murine models [ 60 , 61 ].…”
Section: Pscs-derived Mature Lineage Cells In Clinical Applicationmentioning
confidence: 99%